2015
DOI: 10.5489/cuaj.2790
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with ketamine-based analgesia in patients undergoing robotic radical cystectomy and diversion

Abstract: Introduction: We instituted a ketamine-predominant analgesic regimen in the peri-and postoperative periods to limit the effects of narcotic analgesia on bowel function in patients undergoing radical cystectomy. The primary end points of interest were time to return of bowel function, time to discharge, and efficacy of the analgesic regimen. Methods: We performed a retrospective chart review of patients undergoing robotic-assisted laparoscopic cystectomy (RARC) with urinary diversion by a single surgeon at our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…a profound paralytic ileus developing in patients treated with ketamine for severe bronchospasm (Amoroso and Best, 1989). Another more recent study showed that when ketamine-predominant, opioid minimizing perioperative pain control protocol was used the median time to return of bowel function was 3 days, as opposed to 6 days with an opioid-predominant analgesic regimen (Jacobsohn et al, 2015). Randomized controlled trials showed the incidence of ileus associated with intravenous ketamine use for postoperative analgesia in patients undergoing laparoscopic cholecystectomy (Ye et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…a profound paralytic ileus developing in patients treated with ketamine for severe bronchospasm (Amoroso and Best, 1989). Another more recent study showed that when ketamine-predominant, opioid minimizing perioperative pain control protocol was used the median time to return of bowel function was 3 days, as opposed to 6 days with an opioid-predominant analgesic regimen (Jacobsohn et al, 2015). Randomized controlled trials showed the incidence of ileus associated with intravenous ketamine use for postoperative analgesia in patients undergoing laparoscopic cholecystectomy (Ye et al, 2017).…”
Section: Discussionmentioning
confidence: 99%